Penguatan Sistem Pengendalian Perencanaan Pembangunan Daerah melalui Transformasi E-Pengendalian Menjadi Early Warning System - Hendrik Kresnawan (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effectiveness of regional development planning control systems and to identify gaps between planning documents and the realization of programs/activities in Southeast Sulawesi Province. The study employs a descriptive qualitative approach using secondary data, including planning documents (RKPD, Renstra), reports on program realization from regional agencies, and monitoring data from the e-Control system. The analytical methods applied include gap analysis, APKL analysis, USG analysis, and problem tree analysis. The results indicate significant discrepancies between planning and implementation, reflected in deviations between targets and realizations, delays in priority activities, back-loaded budget absorption patterns, and disparities in performance among regional agencies. Furthermore, the e-Control system has not been optimally utilized as an early detection and continuous control instrument. The findings also reveal that the issues are not only technical but also systemic and structural, particularly due to the suboptimal function of the system as an early warning mechanism.This study recommends strengthening the e-Control system as a real-time early warning system, establishing deviation thresholds, enhancing the capacity of regional agencies, and integrating planning and budgeting information systems to improve consistency and effectiveness in regional development implementation.